2021
DOI: 10.1186/s12974-021-02257-1
|View full text |Cite
|
Sign up to set email alerts
|

Dexamethasone enhances the efficacy of atorvastatin in inhibiting excessively inflammation-induced abnormal angiogenesis by regulating macrophages

Abstract: Background We have recently showed that atorvastatin (ATO) combined with low dose of dexamethasone (DEX) was more efficacious in treating patients with chronic subdural haematoma (CSDH) than ATO monotherapy. This study was designed to investigate the underlying mechanisms of the improved efficacy of this combined therapy. Methods Mass spectrometry was performed to quantitatively detect drugs in haematoma fluids and serum samples from CSDH patients … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
8
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 12 publications
(8 citation statements)
references
References 54 publications
(93 reference statements)
0
8
0
Order By: Relevance
“…However, beyond the hypolipidemic property, recent studies have also demonstrated that ATV has neuroprotective effects as the result of anti-inflammatory, antioxidant, and immunomodulatory activities [15][16][17]. Meanwhile, in our previous study [7], ATV can be detected in the hematoma fluid in CSDH patients and the concentration up to 40 ng/mL, thus raising the question of whether or not ATV can penetrate the blood-brain barrier (BBB). A hematoma is an encapsulated collection of fluid, blood, and blood degradation products layered between the arachnoid and dura mater.…”
Section: Discussionmentioning
confidence: 87%
See 1 more Smart Citation
“…However, beyond the hypolipidemic property, recent studies have also demonstrated that ATV has neuroprotective effects as the result of anti-inflammatory, antioxidant, and immunomodulatory activities [15][16][17]. Meanwhile, in our previous study [7], ATV can be detected in the hematoma fluid in CSDH patients and the concentration up to 40 ng/mL, thus raising the question of whether or not ATV can penetrate the blood-brain barrier (BBB). A hematoma is an encapsulated collection of fluid, blood, and blood degradation products layered between the arachnoid and dura mater.…”
Section: Discussionmentioning
confidence: 87%
“…Our previous study has demonstrated that DXM can enhance the anti-inflammatory and -angiogenic activities of ATV by increasing the ATV level in hematoma fluid and serum and by regulating the functions of macrophages [7]. However, the underlying mechanism of how DXM increases the presence of ATV in hematoma fluid and serum is still unknown.…”
Section: Introductionmentioning
confidence: 99%
“…Previous studies have shown that it may inhibit angiogenesis by reducing inflammatory reactions in tissue. 32 In keloid, dexamethasone can effectively inhibit the expression of VEGF and the proliferation of fibroblasts. 33 Another study demonstrates that dexamethasone can inhibit the expression of VCAM-1 in rats.…”
Section: Discussionmentioning
confidence: 99%
“…In fact, there is increasing evidence to have proven the efficacy of atorvastatin in treating CSDH in recent years. [19,20,22,24,39,40] Atorvastatin can increase circulating endothelial progenitor cells (EPCs) and regulatory T cells (Tregs), promote vessel repair and improve neural function. [41,42] In animal models, [9,[41][42][43] atorvastatin reduces hematoma primarily by suppressing local inflammation, can lower TNF-α and IL-6 levels and can decrease the expression of the VEGF gene .…”
Section: Discussionmentioning
confidence: 99%